Oceanic Electrical Conductivity Variability From Observations and Its Budget From an Ocean State Estimate - D. S. Trossman; R. H. Tyler (Geophysical Research Letters)
Abstract Because spatio‐temporal variations in ocean heat content (OHC) are strongly predicted by ocean conductivity content (OCC) over most of the global ocean, we analyze the dynamical budget and behavior of the electrical conductivity of seawater. To perform these analyses, we use an ocean‐model state estimate designed to accurately represent long‐term variations in ocean properties in a dynamically and kinematically consistent way. We show that this model accurately reproduces the spatio‐temporal variations in electrical conductivity seen in satellite‐derived data and in a seasonal climatology product derived from in‐situ data, justifying use of the model data to perform further analyses. An empirical orthogonal function analysis suggests that the vast majority of the variance in OHC and OCC can be explained by similar mechanisms. The electrical conductivity budget's most important term is the temperature forcing tendency term, suggesting that ocean heat uptake is the mechanism responsible for the strong relationship between OCC and OHC.